Pengaruh Ketersediaan Fasilitas Dan Kualitas Layanan Terhadap Kepuasan Pasien Pada Unit Instalasi Gawat Darurat Rumah Sakit Sele Be Solu Kota Sorong - Kbarek, Eugenia; Muskita, Susana Magdalena Welly (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to analyze the effect of facility availability and service quality on patient satisfaction in the emergency installation unit of Celebesolu Hospital, Sorong City. Using a quantitative method, with a total of 94 respondents. The sampling technique in this study uses systematic sampling. The data collection method in this study uses a questionnaire. The data analysis method uses descriptive analysis method and multiple linear regression analysis. It is processed using the help of the SPSS program. The results of the study show that the variables of facility availability and service quality on patient satisfaction in the emergency installation unit of Selebesolu Hospital, Sorong City simultaneously have a positive and significant influence on patient satisfaction who receive treatment at the Emergency Apparatus of Sele Be Solu Hospital. The Adjusted RS value of 0.595 means 59.5%, indicating that the variable of patient satisfaction can be explained by hospital facilities and service quality. While the remaining 40.5% can be explained by other factors that were not studied in this study.